KEANEKARAGAMAN KHAMIR PENDEGRADASI MINYAK HASIL ISOLASI DARI PELABUHAN TANJUNG PERAK SURABAYA - Tri Nurhariyati; Ni’matuzahroh Ni’matuzahroh; Tini Surtiningsih (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2004)
The aims of this research was to obtain diversity of hydrocarbonoclastic yeast isolated from Tanjung perak harbor Surabaya. Exploration of yeast was conducted by isolation and identification of isolated yeast. Identification of yeast based on characteristics of colonies, cell shape, and biochemical tests. From this research, it was obtained 9 hydrocarbonoclastic yeasts. They were 8 generas: Rhodotorula, Candida, Geotrichum, Torulopsis, Trichosporon, Cryptococcus, Debaryomyces, and Saccharomyces.